Localized Nb clusters in U-Nb liquid alloys: An ab initio molecular dynamics study. (March 2021) - Shi, Yongpeng; Liu, Mingfeng; Wang, Jiantao; Ma, Hui; Li, Ronghan; Chen, Yun; Mo, Wenlin; Li, Dianzhong; Bai, Bin; Wang, Xiaolin; Fa, Tao; Chen, Xing-Qiu
Highlights: Investigation of atomic distributions of U-Nb liquid alloy by AIMD. The volumetric expansion ratios of U-Nb liquid alloy at various temperatures are presented. The existence of localized Nb clusters in UNb liquid alloy is evidenced. Abstract: By means of ab initio molecular dynamics (AIMD), we have evidenced the formation of the localized Nb clusters in the U-Nb liquid alloys even with the very low Nb concentrations. These localized Nb clusters are characterized, qualitatively and quantitatively, in terms of the pair correlation function, structure factor, coordination number and chemical short-range order parameters. The existence of the first highest peaks of the partial Nb-Nb pairs in both their pair correlation functions and structure factors reveals that the Nb atoms prefer to accumulate themselves together to form various localized clusters with three typical Nb networks of Nb2 dimers, opening chains (Nb3 or Nb4 chains) and closed triangles (Nb3 triangles) in the U-Nb liquid alloys. These Nb-Nb affinitive facts are further supported by the derived negative Nb-Nb chemical short-range order parameters. In contrast, both U-U and U-Nb interactions in these liquid alloys are further revealed to have the nearly zero, or positive, chemical short-range order parameters, corresponding to a relatively weak U-U, or repulsive U-Nb, interactions in the U-Nb liquid alloys.